Migration -Trafficking nexus in Post-Soviet Tajikistan - Chatterjee, Sanchita (European Scientific Journal, ESJ, 2021)
Human trafficking, for the manipulation of migrant labour, is a violation of human rights. The spike in human trafficking is partly due to the rapid expansion of labour migration in the neoliberal period. The former Soviet zone has become one of the world’s major human migration sections in the last decade. The article analyses the case of migration and trafficking in Tajikistan as remittances amounted to nearly half of the country’s gross domestic product. In Tajikistan, lack of economic prospects, increasing poverty level, presence of blurred boundaries, leads to the cycle of illicit migration flows which resulted in human trafficking. Human trafficking is a multidimensional issue exacerbated in the countries of destination by poverty and gaps in economic openings versus unmet labour hassles and stern migration commandments. The migration of the Tajik people shortly began after the independence of the country and largely to support subsistence to the families leaving behind. Majority of these migrants prefer Russian federation as their main destination to work where corruption and human trafficking problem is huge. There are limited governing bodies to regulate recruiters’ activities, so migrant workers are at the mercy of recruiters who are known to charge exorbitant fees that indebted migrant worker before arriving in their destination countries. Labour trafficking is a global humanitarian issue but there is scarcely any quantitative research on the issue. This study examined labour abuse indicators among migrant Tajik workers in the Russian Federation and the subsequent human trafficking risks with fresh vulnerabilities created by the economic crises and the covid-19 pandemic in 2020.